Penggunaan Canva Sebagai Media Pembelajaran Di TK Rahayu Kaliurip - Wahyu Ari Setyarini; Najanuddin Najanuddin (Lembaga Riset dan Inovasi Almatani, 2026)
An engaging learning medium is one of the key factors determining the success of the learning process in early childhood education, particularly in kindergartens located in rural areas with limited supporting facilities. This study aims to describe the implementation process, children's responses, and the challenges of using Canva as a learning medium at TK Rahayu Kaliurip, Bener District, Purworejo Regency. The study employed a descriptive qualitative approach, with data collected through observations, interviews, and documentation involving two teachers and twelve Group B children. Data were analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings reveal that teachers utilized Canva to create simple visual learning materials, such as alphabet cards, number cards, and thematic posters tailored to daily learning activities. These materials were either printed or displayed on the teacher's smartphone due to the limited availability of digital devices at the school. The use of Canva-based learning media increased children's enthusiasm, attention, and participation in classroom activities compared with the manually prepared picture media previously used. The main challenges identified were limited internet connectivity, inadequate digital devices, and the need to improve teachers' digital competencies. These findings are consistent with the context of rural kindergartens, where teachers primarily function as the sole intermediaries between digital technology and children, unlike urban kindergartens where children are more likely to have direct access to digital devices. The study concludes that Canva can be effectively utilized as a learning medium in rural kindergartens when adapted to existing infrastructural limitations. It also recommends the provision of digital literacy training for early childhood education teachers in rural areas.